ANDIR AS A SCARED DANCE AT TISATA VILLAGE, KERAMBITAN, TABANAN REGENCY - Arshiniwati, Ni Made (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2014)
Tariandir in the village Tista is a form of Legong Kraton tarisejenis the Tista community called andir.Strukturkoreografinyasangatdekatdengantarilegongkeraton , tetapitari Andir only flourish in the village Tista Kerambitan.Tari inidifungsikan as guardian and bebali art that in the play always involves Rangda sungsungan society , baikditampilkansebagaibagiandariceritamaupunhanyasebagai